Research and development in intelligent systems XXVII incorporating applications and innovations in intelligent systems xviii : proceedings of AI-2010, The thirtieth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence - SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence (Springer London, 2011)
The papers in this volume are the refereed papers presented at AI-2010, the Thirtieth SGAI International Conference on Innovative Techniques and Applications of Artificial Intelligence, held in Cambridge in December 2010 in both the technical and the application streams. They present new and innovative developments and applications, divided into technical stream sections on Intelligent Agents; Knowledge Discovery and Data Mining; Evolutionary Algorithms, Bayesian Networks and Model-Based Diagnosis; Machine Learning; Planning and Scheduling, followed by application stream sections on Applications of Machine Learning I and II; AI for Scheduling and AI in Action. The volume also includes the text of short papers presented as posters at the conference. This is the twenty-seventh volume in the Research and Development in Intelligent Systems series, which also incorporates the eighteenth volume in the Applications and Innovations in Intelligent Systems series. These series are essential reading for those who wish to keep up to date with developments in this important field. Research and development in intelligent systems XXVII best technical paper -- Intelligent agents -- Knowledge discovery and data mining -- Planning and scheduling -- Machine learning -- Evolutionary algorithms, bayesian networks and model-based diagnosis -- Short papers. Application and innovations in intelligent systems XVIII best application paper -- Applications of machine Learning I -- Applications of machine learning II -- AI for scheduling -- AI in action.- Short papers.